Perkembangan dan Pemetaan Riset Wakaf Produktif: Analisis Bibliometrik - Azwar, Azwar; Khaerul Aqbar (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
This study aims to map and analyze the development of research on productive waqf using bibliometric methods in reputable international publications. The research employs quantitative methods through bibliometric analysis on the Scopus database from 2004 to 2024. The results show a significant increase in publications on productive waqf in recent years. The most productive author/researcher in this area and the most frequently cited is A. Ascarya. In terms of publication media, the Journal of Islamic Accounting and Business Research has emerged as a popular platform. Topic mapping results reveal that the keyword